Multicentre factorial randomized clinical trial of perioperative immunonutrition versus standard nutrition for patients undergoing surgical resection of oesophageal cancer. Issue 10 (12th July 2018) - Mudge, L A; Watson, D I; Smithers, B M; Isenring, E A; Smith, L; Jamieson, G G; Aly, A; Archer, S; Ballal, M; Barbon, J; Barbour, A; Benton, K; et al.
Abstract: Background: Preoperative immunonutrition has been proposed to reduce the duration of hospital stay and infective complications following major elective surgery in patients with gastrointestinal malignancy. A multicentre 2 × 2 factorial RCT was conducted to determine the impact of preoperative and postoperative immunonutrition versus standard nutrition in patients with oesophageal cancer. Methods: Patients were randomized before oesophagectomy to immunonutrition (IMPACT®) versus standard isocaloric/isonitrogenous nutrition, then further randomized after operation to immunonutrition versus standard nutrition. Clinical and quality-of-life outcomes were assessed at 14 and 42 days after operation on an intention-to-treat basis. The primary outcome was the occurrence of infective complications. Secondary outcomes were other complications, duration of hospital stay, mortality, nutritional and quality-of-life outcomes (EuroQol EQ-5D-3 L™, European Organisation for Research and Treatment of Cancer (EORTC) QLQ-C30 and EORTC QLQ-OES18). Patients and investigators were blinded until the completion of data analysis. Results: Some 278 patients from 11 Australian sites were randomized; two were excluded and data from 276 were analysed. The incidence of infective complications was similar for all groups (37 per cent in perioperative standard nutrition group, 51 per cent in perioperative immunonutrition group, 34 per cent in preoperative immunonutrition group and 40 per cent in postoperative immunonutrition group; P = 0·187). There were no significant differences in any other clinical or quality-of-life outcomes. Conclusion: Use of immunonutrition before and/or after surgery provided no benefit over standard nutrition in patients undergoing oesophagectomy. Registration number: ACTRN12611000178943 (https://www.anzctr.org.au ). Abstract : No difference